PEMANFAATAN EKSTRAK BIJI KESUMBA KELING ( Bixa orellana L) SEBAGAI PEWARNA ALAMI PADA SEDIAN LIPSTIK - luky dharmayanti (Sekolah Tinggi Kesehatan Al-Fatah Bengkulu, 2020)
Lipstick (Lipstick) is a cosmetic sedan that is used to color the lips with an artistic touch so as to enhance aesthetics in facial makeup. One of the plants that can be used as natural dyes is kelumba keling (Bixa orellana L). Kesumba rivet contains bixsin and nonbixin compounds, which can be used as natural dyes that have the potential as antioxidants. The aim of this study is to utilize kelumba keling as a natural coloring agent in lipstick sedans.Making Keeling keumba seed extract by maceration using 70% ethanol as a solvent. The formulation was made by means of a lipstick base added with variations in the concentration of kesumba keling seed extract 18%, 20%, 22%. Tests carried out on a lipstick sedan made include organoleptic test, irritation test, PH test, melting point test, lipstick sediment test , during storage for 30 days.The results of the test of the lipstick extract of the kesumba rivet seed in the stable orange color organoleptic test can be seen in the irritation test of the non-irritating lipstick sedan, at the melting point test at 51oC for 15 minutes formulation F0, F1, F2, F3 the lipstick made can melt, at Sedian rub test was carried out 5 times basting. In this study it can be concluded that the kesumba keling seed extract can be used as a natural coloring agent in lipstick sedans. Kata Kunci : Biji Kesumba Keling, Lipstik, Evaluasi lipstik